Hardware Trojan Detection and Mitigation in NoC using Key authentication and Obfuscation Techniques - Thejaswini P; Vivekananda G; Anu H; Priya R; Krishna Prasad B S; Nischay M (EMITTER International Journal of Engineering Technology, 2022)
Today's Multiprocessor System-on-Chip (MPSoC) contains many cores and integrated circuits. Due to the current requirements of communication, we make use of Network-on-Chip (NoC) to obtain high throughput and low latency. NoC is a communication architecture used in the processor cores to transfer data from source to destination through several nodes. Since NoC deals with on-chip interconnection for data transmission, it will be a good prey for data leakage and other security attacks. One such way of attacking is done by a third-party vendor introducing Hardware Trojans (HTs) into routers of NoC architecture. This can cause packets to traverse in wrong paths, leak/extract information and cause Denial-of-Service (DoS) degrading the system performance. In this paper, a novel HT detection and mitigation approach using obfuscation and key-based authentication technique is proposed. The proposed technique prevents any illegal transitions between routers thereby protecting data from malicious activities, such as packet misrouting and information leakage. The proposed technique is evaluated on a 4x4 NoC architecture under synthetic traffic pattern and benchmarks, the hardware model is synthesized in Cadence Tool with 90nm technology. The introduced Hardware Trojan affects 8% of packets passing through infected router. Experimental results demonstrate that the proposed technique prevents those 10-15% of packets infected from the HT effect. Our proposed work has negligible power and area overhead of 8.6% and 2% respectively.